AGE AND GENDER SPECIFIC FEATURES OF SPEECH IN ENGLISH AND UZBEK (Ustozlar uchun, 2026)
This article studies the influence of age and gender factors on speech characteristics in English and Uzbek from a linguistic, sociolinguistic and pragmatic perspective. In modern communication, age-related speech differences, lexical, grammatical and prosodic features characteristic of male and female speech, as well as gender stereotypes in the two languages, their connection with the social function of language and thinking are extensively analyzed. As a research, corpus materials, sociolinguistic observations and conversational texts were compared. According to the results of the article, while gender differences in English are more manifested at the pragmatic and intonational level, in Uzbek their main manifestation is expressed through forms of address, categories of respect and sociocultural units. It is determined that age-related speech differences in both languages ​​differ significantly in metaphorical expression, vocabulary and communicative strategies.